A 'sea anemone' onychomatricoma. (September 2021) - Zhu, Xi Ming; AlBadry, Waleed; Fleming, Andrew
Abstract: Objective: Here we describe the presentation, identification, operation details and subsequent histological analysis of an onychomatricoma, a benign rare subungual tumour that is often misidentified and diagnosed. Methods: No public involvement to declare, patient was consented for surgical excision and provided verbal consent to photography and its use in publishing. Participant: One 44-year-old female. Intervention: One time surgical excision. Primary and secondary outcomes measured: Not applicable. Results: Complete excision and histopathological report of specimen provided. Conclusion: Complete surgical excision is an effective means of treatment for onychomatricoma.